IMPLEMENTASI PROGRAM KAMPUS MENGAJAR ANGKATAN 6 DALAM MENINGKATKAN KOMPETENSI PESERTA DIDIK DI SD NEGERI 200/IX BUKIT MULYA - Arista Mukti, Rayi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Online learning carried out during the Covid-19 pandemic has caused most students to experience learning loss or loss of knowledge and skills (literacy and numeracy). One of the government's steps to overcome this is by introducing the Independent Learning Campus (MBKM) policy in one of its programs, the Teaching Campus. One of the partners of the Teaching Campus Program for Class 6 is SD Negeri 200 IX Bukit Mulya. The aim of carrying out this research is to determine the impact of implementing the Class 6 Teaching Campus program, especially on the development of literacy and numeracy skills as well as adaptation to technology. The method used in this research is qualitative and data collection techniques include observation, interviews and documentation. This research covers all students at the assigned school, a total of 134 students. Based on the results of these observations, a work program was prepared. From the implementation of the work program, satisfactory results were obtained, there was an increase in student competence, especially in literacy and numeracy skills which were visible during the implementation of class AKM as well as the growth of good character in students. Based on this progress, it can be concluded that the work program that the author implemented in the Teaching Campus Program has succeeded in bringing positive impacts and changes in the world of education.